A associação comunitária e de micro produtores rurais de São Pedro de Joselândia : um estudo sobre trabalho e produção de saberes - Azeredo, Eloisa Rosana de (2013)
The objective of this research is to reflect the work and its mangling caused by the capitalist mode of production in a traditionalcommunity of “São Pedro de Joselândia” in the North of “Pantanal region” at “Mato Grosso” state. This community follows the women's organization of the Community Association of Micro and Rural Producers of São Pedro de Joselândia. Seeking the perspectiveof popular economy work corporately. Taking the method as historical materialism and dialectical we believe that the Popular Economy is a phenomenon that deserves to be focused forward to the economical, political and social changes that reshape the worldof work. Reflect the meaning of work and its relationship with education, understanding it as the essence of his whole historical process. In this construct a trajectory that moves through the process of mangling job by the modes of production historically constructed, where intellectual work and manual are dichotomized in favor of the capitalist system. The women of the community had the dream of setting up an association where everyone could work together, as in former relationships identified in Joselândia: no boss, no clock, no oppression, producing what they like in a relationship of pleasure, exchange and creation. We make explicit the associated work as an opportunity to recover the relations generating a new work culture. Through oral histories of women of the Association, as well as other residents of the Community of St. Peter Joselândia, we seek to learn a little of their stories, as well as their expectations of the work associated with it, due to conflicts, needs and constraints failed to materialize. Even without having been able to realize his project of human emancipation, we analyze the cultural richness of immaterial production developed by this process and associated Community recognition from the construction of the most varied knowledge, processed and disseminated in the various relationships established in the planning process of the Association.